Gewalt als soziales Problem in Schulen - Melzer, Wolfgang (Verlag Barbara Budrich, 2006)
The book includes an analysis and presentation of forms, extent and causes of school violence. In addition, the possibilities of violence prevention and intervention in schools are presented. The first edition (out of print) was published in 1998 by Leske + Budrich, Opladen.